Disciplinary Convergence in Systems Engineering Research - Madni, Azad M.; Boehm, Barry; Ghanem, Roger G.; Erwin, Daniel; Wheaton, Marilee J. (Springer International Publishing : Imprint: Springer, 2018)
The theme of this volume on systems engineering research is disciplinary convergence: bringing together concepts, thinking, approaches, and technologies from diverse disciplines to solve complex problems. Papers presented at the Conference on Systems Engineering Research (CSER), March 23-25, 2017 at Redondo Beach, CA, are included in this volume. This collection provides researchers in academia, industry, and government forward-looking research from across the globe, written by renowned academic, industry and government researchers.